Determination and Pharmacokinetics of 2"-O-Rhamnosylswertisin in Rat Plasma by RP-LC - Teng, Z.Q.; Li, Y.J.; Dai, R.J.; Gu, H.; Fu, H.Q.; Yu, Y.H.; Chen, Y.; Meng, W.W.; Deng, Y.L. (Asian Journal of Chemistry, 2011)
A simple, rapid and sensitive HPLC-UV method for determining 2"-O-rhamnosylswertisin in rat plasma was developed. Sample preparations were carried out by protein precipitation with acetonitrile, followed by the evaporation of the acetonitrile to dryness. The analyses were carried out on a Kromasil C18 (250 mm × 4.6 mm, 5 μm) column kept at room temperature (25 ± 3 ºC) using a mobile phase composed of acetonitrile-water-glacial acetic acid (19.9:80:0.1, v/v/v). The flow rate was 1 mL min-1. The recovery, stability, inter- and intra-day precisions and accuracy for all samples were satisfactory. The method was applied to the pharmacokinetics study of 2"-O-rhamnosylswertisin after oral administration of 13 g kg-1 Belamcanda chinensis leaves extract to Wistar rats. Pharmacokinetics after intravenous administration of 10 mg kg-1 of 2"-O-rhamnosylswertisin and the absolute bioavailability was also studied.